AIR POLLUTION IN UZBEKISTAN AND TECHNOLOGICAL MEASURES USED IN ITS PREVENTION (Intent Research Scientific Journal, 2023)
Atmospheric pollution means changes in its composition and properties that have a negative impact on human health, animals, plants and ecosystems. The atmosphere is polluted by natural and artificial means. Volcanic eruptions, dust, forest, steppe, plant dust, microorganisms, cosmic dust, etc. are natural sources of pollution. Energy is a source of artificial pollution. Industrial enterprises, transport, household waste, etc. Currently, 75% of atmospheric pollution comes from natural sources and 25% from anthropogenic sources.